2019
DOI: 10.3991/ijet.v14i18.11332
|View full text |Cite
|
Sign up to set email alerts
|

Application of a New Cultivation Model in an Undergraduate 'Convention and Exhibition Management' Study Program

Abstract: Convention and exhibition management is a practical and emerging new major in colleges and universities. Students are required to master strong practical and comprehensive coordination skills. However, the professional demand of the convention and exhibition industry cannot be met under the traditional general education training model. Hence, the present study combines the professional work-oriented undergraduate training with the cooperative education concept and proposes the industry accreditation plus gover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…70 schools in Canadian regions were randomly surveyed, and the data obtained through 8-month follow-up observations showed that strengthening home-school communication can solve students' multiple Learning problems [15]. Zhang, H. et al put forward the cultivation concept of cooperation between students and higher education that combines professional work and undergraduate training, and for the exhibition management profession, put forward the cooperative training mode of industry certification + government consulting, realizing the four-in-one critical paths of the government, school, industry, and students, and the optimization and reform of the student training mechanism, which improved the students' comprehensive literacy [16]. This paper first analyzes the structure and principles of web crawler technology in depth and then adopts this technology to obtain research data on higher education management and student cultivation.…”
Section: Introductionmentioning
confidence: 99%
“…70 schools in Canadian regions were randomly surveyed, and the data obtained through 8-month follow-up observations showed that strengthening home-school communication can solve students' multiple Learning problems [15]. Zhang, H. et al put forward the cultivation concept of cooperation between students and higher education that combines professional work and undergraduate training, and for the exhibition management profession, put forward the cooperative training mode of industry certification + government consulting, realizing the four-in-one critical paths of the government, school, industry, and students, and the optimization and reform of the student training mechanism, which improved the students' comprehensive literacy [16]. This paper first analyzes the structure and principles of web crawler technology in depth and then adopts this technology to obtain research data on higher education management and student cultivation.…”
Section: Introductionmentioning
confidence: 99%